TELAAH METODOLOGI PENYAHIHAN IBNU HIBBANTERHADAP HADIS ((اقْرَؤُوا عَلَى مَوتَاكُم يس)) - Noor Ikhsan Silviantoro; Sucipto; Ikmal (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2019)
When talking about the validation of the hadith in detail, we will understand that there are five conditions agreed upon by the clerics, and there are also additional conditions or comparisons made by some scholars.Among the scholars who have different conditions for the validation of hadith is Ibn Hibban. He has the requirements of saheeh traditions which are quite unique, which are very tight and very loose. So that with it appeared friction in establishing the keshahihan of several traditions in the Saheeh book with other scholars. This is what drives us to conduct this research. The goal is that we can find out how the methodology of Ibn Hibban in validating the hadith, how the views of scholars in assessing his methodology, and examples of disputed traditions.This study uses a qualitative approach, where we try to present a complete picture of the problems being discussed by exploring and clarifying several different views directly from the primary source, then we use analysis, to produce conclusions that can be accounted for. And we use non-interactive types of research, which do not collect data except through analysis of documents and libraries and do not involve interaction with respondents. With this research, a number of conclusions were produced, namely the methodology of Ibn Hibban considered mutasahil in giving the requirements of the saheeh hadith agreed upon by the ulama, which allowed the Majhul narrative to be in the tsiqah category, and this was criticized by the scholars. Among the examples of the hadith is the hadith about Yasin, so that the degree is weak.